Making copies in European art, 1400-1600 : shifting tastes, modes of transmission, and changing contexts - Bellavitis, Maddalena; Bellavitis, Maddalena (Brill's studies in intellectual history, 2018)
Inhaltsverzeichnis: Jan van Eyck's Arnolfini portrait and copies after his Woman and her toilette : recollections of the Alhambra's constellation halls, the hamman, and alchemy / Barbara von Barghahn -- Not just copies but variations, suggestions, interpretations and critical reception : Joos van Cleve and the lost Madonna of the cherries by Leonardo da Vinci / Mari Pietrogiovanna -- Pictorial copies in Granada during the early modern age / David García Cueto